2001
DOI: 10.1123/ijsnem.11.2.258
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplements as a Source for Positive Doping Cases?

Abstract: We report the findings of the analysis of 75 different nutritional supplements bought through the internet. Seven products (all from the class of prohormones) contained other hormone substances than indicated on the labels, and two further products contained ephedrine and caffeine without a clear indication on the labels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
12

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 5 publications
3
53
0
12
Order By: Relevance
“…Supplement 20 listed HMB on the label, but when it was tested low amounts of 4-androstenedione and 19-nor-4-androstenedione were found. Kamber et al 6 analysed 75 different nutritional supplements and found that more than 9% contained hormonal substances not listed on the labels, a finding similar to this study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Supplement 20 listed HMB on the label, but when it was tested low amounts of 4-androstenedione and 19-nor-4-androstenedione were found. Kamber et al 6 analysed 75 different nutritional supplements and found that more than 9% contained hormonal substances not listed on the labels, a finding similar to this study.…”
Section: Discussionsupporting
confidence: 79%
“…4 Results from an International Olympic Committee (IOC) study 5 on nutritional supplements (13 countries excluding South Africa) showed that 94 (14.8%) of 634 samples contained prohormones not listed on the label. Both Catlin et al 1 and Kamber et al 6 analysed nutritional supplements and found hormone contaminants not listed on the labels. This may explain the recent increase in positive doping cases.…”
Section: Billion a Year (Health Products Association Of South Africa mentioning
confidence: 99%
“…Bazı çalışmalarda ürünle-rin etiket üzerinde belirtilmeyen maddelerle kontaminasyonu veya etikette belirtilen miktarın çok daha fazlasını içerdiği bildirilmektedir. 51,52 SONUÇ Spor salonlarında BDÜ kullanıcılarının büyük ço-ğunluğunun ürünler hakkında antrenörlerine gü-veniyor olması uzman rehberliğinin yetersizliğini ve ciddi bir halk sağlığı endişesini yansıtmaktadır. Bireylere ürünler hakkında en doğru bilgiyi sağla-yacak meslek grubu diyetisyenlerdir.…”
Section: Beslenme Destek üRünleri̇ni̇n Kullanimi Ve Kullanilan üRünleri̇unclassified
“…More alarming results were obtained in the same studies as it was proven that in several supplements additional steroids, or precursors, other than the labelled prohormones were present. Results from Kamber et al (2001) show that 35 % (six out of seventeen) of prohormone supplements contain other substances than indicated on the label. Analysis of a 1-androstene3b,17b-diol-containing nutritional supplement revealed the presence of five other anabolic steroids including boldenone and testosterone .…”
Section: Prohormones and Anabolic Androgenic Steroidsmentioning
confidence: 99%
“…These methods include TLC (Dutt & Poh, 1981), immunoassays (Ros et al 1999;Kamber et al 2001), GC (Betz et al 1997;Hansen, 2001;Wiedemer & Thrall, 2004), HPLC (Gurley et al 1998;Hurlbut et al 1998;Okamura et al 1999;Haller et al 2004a;Jacob et al 2004;Li et al 2002;Trujillo & Sorenson, 2003;Roman & Walther, 2004) and capillary electrophoresis (Flurer et al 1995). Identification is best achieved using MS.…”
Section: Analysis Of Nutritional Supplements For Doping Contaminantsmentioning
confidence: 99%